Mechanisms Of Adaptation Of Small Mammals In Natural Biotes (Texas Journal of Agriculture and Biological Sciences, 2025)
The article assesses the adaptation mechanisms of small mammals in the natural biota of the Southern Aral Sea region to environmental conditions. Small mammals are an indicator species that respond with sensitivity to environmental factors (temperature, humidity, soil properties, anthropogenic factors). Depending on environmental factors, adaptation mechanisms are formed in their population.